2010
DOI: 10.1007/s00125-010-1856-z
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase inhibits IL-6-stimulated inflammatory response in human liver cells by suppressing phosphorylation of signal transducer and activator of transcription 3 (STAT3)

Abstract: Aim/hypothesis The aim of the study was to examine the possible role of AMP-activated protein kinase (AMPK) in the regulation of the inflammatory response induced by cytokine action in human liver cells. Methods IL-6-stimulated expression of the genes for acutephase response markers serum amyloid A (SAA1, SAA2) and haptoglobin (HP) in the human hepatocarcinoma cell line HepG2 were quantified after modulation of AMPK activity by pharmacological agonists (5-amino-4-imidazolecarboxamideriboside [AICAR], metformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 53 publications
(61 reference statements)
3
67
0
Order By: Relevance
“…For example, others have shown that chronic AMPK activation in hepatocytes with metformin for 12 hr is able to increase levels of the orphan nuclear receptor small heterodimer partner (SHP), which reduces STAT3 phosphorylation on Tyr705 and co-localizes with nuclear STAT3 to reduce its binding to target gene promoters (53) (54). Similarly, others have demonstrated that chronic treatment of hepatocytes with AICAR suppresses IL-6 signaling, and was thought to involve an AMPK-mediated inhibition of IL-6-stimulated Tyr phosphorylation and activation of JAK1 and JAK2, and that depletion of AMPKα1 and α2 subunits could block the inhibitory effects of AMPK activators on cytokine-stimulated signaling without significantly altering basal activation (55) (56). However the underlying mechanisms were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, others have shown that chronic AMPK activation in hepatocytes with metformin for 12 hr is able to increase levels of the orphan nuclear receptor small heterodimer partner (SHP), which reduces STAT3 phosphorylation on Tyr705 and co-localizes with nuclear STAT3 to reduce its binding to target gene promoters (53) (54). Similarly, others have demonstrated that chronic treatment of hepatocytes with AICAR suppresses IL-6 signaling, and was thought to involve an AMPK-mediated inhibition of IL-6-stimulated Tyr phosphorylation and activation of JAK1 and JAK2, and that depletion of AMPKα1 and α2 subunits could block the inhibitory effects of AMPK activators on cytokine-stimulated signaling without significantly altering basal activation (55) (56). However the underlying mechanisms were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The direct anti-inflammatory action of metformin has been reported in several animal experimental studies, both in the liver (69,54,47) and in circulating polymorphonuclear cells (9). In contrast to these experimental findings, metformin efficiency in human NASH treatment is the subject of open debate (58,60).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis Western blot analysis was performed as previously described [10]. See the ESM Methods for further details on procedures and antibodies used.…”
Section: Methodsmentioning
confidence: 99%